KARAKTERISTIK DAN KOMPETENSI PERAWAT KESEHATAN JIWA PUSKESMAS DI KOTA MAKASSAR - Harisa, Akbar; Yodang, Yodang; Hidayat, Muhammad; Rahmatullah, Marhamah Putri (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Nursing services are a crucial part of health services in order to achieve optimal health status in every individual, family and community. Lack of nurse competence in mental health services will have an impact on the quality of mental health services. This study aims to determine the relationship between the characteristics and competence of nurses in serving patients with mental health disorders at Primary Health Care. The research design used was a cross-sectional study. The subject of this study was the nurse in charge of the mental health program at each Primary Health Care in Makassar City which was carried out from May to October 2022. A total of 24 Primary Health Care in the Makassar City area so that by applying total sampling, the number of participants or research subjects was 24 people. The results showed that 58.3% of them were competent nurses (novice-expert range), and all variables or subject characteristics showed no relationship with the level of competence of nurses in charge of mental health programs at Primary Health Care. Subjects who fall into the category of competent nurses have attended mental health training, seminars, and have more than 5 years of work experience. To increase the validity of the research data, the number of subjects must be increased, including further research on the influence of other characteristic variables on nurse competence, some of which can be cultural background, institution, or even clustering of the area where nurses work.